SynSynthesis of Bi3TaO7–Bi4TaO8Br composites in ambient air and their high photocatalytic activity upon metal loading† - Chatterjee, Kaustav; Banoo, M.; Mandal, S.; Sahoo, Lipipuspa; Gautam, U.K. (Royal Society of Chemistry, 2019)
Herein, we show that composites of Bi3TaO7–Bi4TaO8X (X = Cl, Br), two important Bi- and Ta-based light-responsive phases, can be prepared by high temperature, ambient air treatment of the precursors including easily oxidizable BiOX that retain the halide phases in excess of 60% and exhibit high photocatalytic activity. Furthermore, when these phases were loaded with less than 1% noble metals (Pd, Pt, Ag), nearly complete separation of the photogenerated excitons was observed, leading to a significant enhancement in the photocatalytic activity.
Keywords: Bi- and Ta-based light; Air treatment; High temperature